Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae) - Jevgeni Jakovlev; Jukka Salmela; Alexei Polevoi; Jouni Penttinen; Noora-Annukka Vartija (Biodiversity Data Journal, 2014)
New faunistic data on fungus gnats (Diptera: Sciaroidea excluding Sciaridae) from Finland and NW Russia (Karelia and Murmansk Region) are presented. A total of 64 and 34 species are reported for the first time form Finland and Russian Karelia, respectively. Nine of the species are also new for the European fauna: Mycomya shewelli Väisänen, 1984, M. thula Väisänen, 1984, Acnemia trifida Zaitzev, 1982, Coelosia gracilis Johannsen, 1912, Orfelia krivosheinae Zaitzev, 1994, Mycetophila biformis Maximova, 2002, M. monstera Maximova, 2002, M. uschaica Subbotina & Maximova, 2011 and Trichonta palustris Maximova, 2002.